Penguatan karakter percaya diri siswa melalui model cooperative learning tipe think pair share di SDN 2 Bayah Timur - Dhara Vallia Putri; Ana Nurhasanah; Reksa Adya Pribadi; Sigit Setiawan (Universitas Sarjanawiyata Tamansiswa, 2026)
Self-confidence is an essential character dimension for elementary school students because it supports communication, social interaction, and active participation in learning. Preliminary observation at SDN 2 Bayah Timur showed that several grade II students were still shy, passive, and hesitant to express ideas in front of the class. This study aimed to describe the process of strengthening students’ self-confidence through the Cooperative Learning model of Think Pair Share, identify implementation challenges, and analyze the success of the strengthening process. The study used a descriptive qualitative approach. Data were collected through classroom observation, semi-structured interviews with the principal and the grade II teacher, and documentation of learning activities. The subjects consisted of 15 grade II students, the grade II teacher, and the principal. Data were analyzed interactively through data reduction, data display, and conclusion drawing. Data validity was strengthened through source and technique triangulation. The findings show that Think Pair Share strengthened students’ self-confidence through three gradual learning experiences: individual thinking, paired discussion, and sharing discussion results in front of the class. Students became more willing to ask questions, answer teacher prompts, discuss with peers, and present group ideas. The main challenges were differences in students’ characteristics, limited learning time, classroom noise, and the need for continuous teacher support for shy students. Teachers addressed these challenges through balanced pairing, role assignment, positive reinforcement, adaptive questioning, and simple learning media. The study concludes that Think Pair Share is relevant for strengthening self-confidence among lower-grade elementary students because it provides a safe, structured, and participatory learning space.